Women Want Freedom Too: The Problem of Male Anarchisms and Socialisms of 1880-1930 in Costa Rica - Flórez-Estrada Pimentel, María (2021)
The male anarchism of the second part of the 19th century and the first part of the Costa Rican 20th can be considered as a radical liberalism because it is a discourse that defies the principle of authority of communitarian patriarchy (catholic and communist). However, the cultural breaking point was produced by feminist anarchism due to its questioning of the sexual order and its demand for equality and freedom also for working women. They defined the “social question” beyond an economic conflict between social classes, although the male hegemony in the press and, later, in the historiography, leaves pending to recover in all its dimension the importance of their challenge. This can be affirmed from the analysis of 115 editions of 10 Costa Rican newspapers published between 1880-1930 that had the purpose of identifying the anarchist discourses on modern sexual identities in that period.